Environmental art and its contribution to establishing an awareness of the sacred in nature - Matthews, Elaine Katherine Simone (Rhodes University, Faculty of Humanities, Department of Fine Art, 2000)
The introduction establishes the goal of the research, which is to discover that art concerned with re-evaluating the relationship to the environment and spirituality can serve to connect people to one another, and to the environment. The context of the research is the contemporary ecological and spiritual crisis of the postmodern world. The background places the discussion within the contexts of modernism and postmodernism. The historical background focuses on the period from the 1960s to the present day. Land and Environmental artists who work in a manner that is conscious of environmental issues and who suggest a sacred and creative attitude to ecology are discussed. My own creative work which is a response to both ancient and contemporary sites as well as to contemporary theories of art and spirituality is discussed. The four projects, are discussed in chronological order, they are: Quest - A journey into Sacred Space; Gaika's Kop - Sacred Mountain; Labyrinth - Journeys to the Centre; and Transforming the Centre. The conclusion shows that the multi-faceted, intertextual and relativistic philosophy of postmodernism has brought about a significant change in the attitude of humanity towards the environment. Artists who reject the modernist aesthetic and philosophy are making art that emphasises relationship to, rather than separation from the natural world.
Keywords: Installations (Art); Art, Modern -- 20th century; Nature (Aesthetics)